2019
DOI: 10.1016/j.ymgmr.2019.100479
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of a patient with lysosomal acid lipase deficiency and first results after initiation of treatment with Sebelipase alfa: A case report

Abstract: We report on a case of very rare autosomal recessive cholesteryl ester storage disease due to lysosomal acid lipase deficiency (LALD). LALD is caused by mutations in the lysosomal acid lipase A ( LIPA ) gene resulting in cholesteryl ester accumulation in liver, spleen, and macrophages. It can lead to liver failure, accelerated atherosclerosis and premature death. Until recently, treatment options were limited to lipid-lowering medications to control dyslipidemia. Presently, a long-term e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…21 Sebelipase alfa (Synageva BioPhar ma Corp., Lexington, MA, United States), a recombinant human LAL, is under development for use as enzymatic replacement therapy. The initial trial in adults showed a decrease in serum lipids and liver volume and normalization of liver transaminases, 22 and a phase 3 global trial is currently under way. 23 Timely diagnosis, as well as incorporation of LAL activity in newborn screening, will be needed to optimize the time to begin enzymatic replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…21 Sebelipase alfa (Synageva BioPhar ma Corp., Lexington, MA, United States), a recombinant human LAL, is under development for use as enzymatic replacement therapy. The initial trial in adults showed a decrease in serum lipids and liver volume and normalization of liver transaminases, 22 and a phase 3 global trial is currently under way. 23 Timely diagnosis, as well as incorporation of LAL activity in newborn screening, will be needed to optimize the time to begin enzymatic replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…International guidelines on the treatment of LAL-D are lacking. In 2012 (recruiting is still in progress), an international registry was started to improve the understanding of therapeutic interventions and their long-term effectiveness ( Soll et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a potential miR-499 target, we identified the gene LIPA, which encodes for the lysosomal acid lipase (LAL), an enzyme responsible for the hydrolysis of triglycerides and cholesteryl esters (CE), resulting in the release of unesterified cholesterol and free fatty acids [ 48 ]. Mutations of LAL have been associated with CE and TG accumulation in the liver, spleen, and macrophages, resulting in liver failure, accelerated atherosclerosis, and premature death [ 49 ]. OSBPL1A, a member of the intracellular lipid receptors, was previously identified as a specific target of miR-499a-5p, and a reduced OSBPL1A activity was associated with a more pro-atherogenic lipid trait characterized by low plasma HDL-C levels [ 7 , 50 ].…”
Section: Discussionmentioning
confidence: 99%